Successful inguinal interstitial brachytherapy in metastatic cervical carcinoma: a case report - Qin, Yi; Guan, Ping; Li, Dan; He, Huailin; He, Wenfeng; Tan, Longjing; Deng, Xiangyu; Liao, Bizhen; Wen, Qinglian; Zhang, Zhenhua (Frontiers in Oncology, 2024)
Background Treatment of metastatic cervical cancer is a tricky issue. Currently, the National Comprehensive Cancer Network (NCCN) guideline recommends chemotherapy combined with bevacizumab for recurrent or metastatic cervical cancer. Still, the recurrence rate is high and the survival rate is low after standard treatment. We urgently need to achieve a multimodal therapy approach for recurrent or metastatic cervical cancer. Case description We report the case of a patient with stage IB2 cervical squamous carcinoma who developed multiple metastases within a short term after receiving first-line standard treatment, and she underwent interstitial brachytherapy after systemic therapy with an encouraging outcome. The patient developed suspected inguinal lymph node metastases after 9 months at the end of first-line therapy and multiple metastases in the inguinal lymph nodes, anterior abdominal wall, and right lung after 17 months. As the patient had residual inguinal lymph nodes after systemic therapy, she received 3D-printed template-guided interstitial brachytherapy to the inguinal lymph nodes and maintenance therapy. By Sep 2023, she had achieved a good treatment outcome with a progression-free survival (PFS) of 36 months. Conclusion Based on our patient response, when multiple metastases develop in the short term in early-stage cervical squamous carcinoma after first-line therapy, we may consider implementing local therapy combined with systemic therapy.